IRF-7 Mediates Type I IFN Responses in Endotoxin-Challenged Mice - Sin, Wei-Xiang; Yeong, Joe Poh-Sheng; Lim, Thomas Jun Feng; Su, I-Hsin; Connolly, John E.; Chin, Keh-Chuang (Frontiers in Immunology, 2020)
IRF-7 mediates robust production of type I IFN via MyD88 of the TLR9 pathway in plasmacytoid dendritic cells (pDCs). Previous in vitro studies using bone marrow-derived dendritic cells lacking either Irf7 or Irf3 have demonstrated that only IRF-3 is required for IFN-β production in the TLR4 pathway. Here, we show that IRF-7 is essential for both type I IFN induction and IL-1β responses via TLR4 in mice. Mice lacking Irf7 were defective in production of both IFN-β and IL-1β, an IFN-β-induced pro-inflammatory cytokine, after LPS challenge. IFN-β production in response to LPS was impaired in IRF-7-deficient macrophages, but not dendritic cells. Unlike pDCs, IRF-7 is activated by the TRIF-, but not MyD88-, dependent pathway via TBK-1 in macrophages after LPS stimulation. Like pDCs, resting macrophages constitutively expressed IRF-7 protein. This basal IRF-7 protein was completely abolished in either Ifnar1-/- or Stat1-/- macrophages, which corresponded with the loss of LPS-stimulated IFN-β induction in these macrophages. These findings demonstrate that macrophage IRF-7 is critical for LPS-induced type I IFN responses, which in turn facilitate IL-1β production in mice.